2019
DOI: 10.1002/jctb.5857
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sound elements on growth, viability and protein production yield in Escherichia coli

Abstract: BACKGROUND The effect of sound on biological systems has been addressed previously in the literature. However, most studies addressing this topic focus on the characterization of the effect of frequency on biological systems. In this regard the effect of other soundwave elements has been overlooked. In the present work, the effects of frequency, amplitude, duration, intermittence and pulse – individually and in combination – were tested with Escherichia coli by measuring biomass, viability and recombinant prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Published results indicate that audible sound (20 Hz-20 kHz) [4] stimulation can directly affect growth and other processes in microbial cultures. For example, audible sound has been reported to affect gramnegative bacteria, by increasing cell viability, colony formation and biomass production [5][6][7][8][9], and increase growth, antibiotic susceptibility, and endospore germination [10]. Audible sound stimulation has also been reported to increase growth, antibiotic susceptibility and the production of industrially relevant compounds in the yeast Candida albicans, and to increase both growth rate and total biomass in microalgae [8,11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Published results indicate that audible sound (20 Hz-20 kHz) [4] stimulation can directly affect growth and other processes in microbial cultures. For example, audible sound has been reported to affect gramnegative bacteria, by increasing cell viability, colony formation and biomass production [5][6][7][8][9], and increase growth, antibiotic susceptibility, and endospore germination [10]. Audible sound stimulation has also been reported to increase growth, antibiotic susceptibility and the production of industrially relevant compounds in the yeast Candida albicans, and to increase both growth rate and total biomass in microalgae [8,11,12].…”
Section: Introductionmentioning
confidence: 99%
“…There are many records documenting how sound affects biomolecules in water solutions, single-cells and even whole organisms, plants especially [ 1 , 2 , 3 , 4 , 5 , 6 , 7 ]. One study showed that audible sound in the form of music (38–689 Hz) was able to affect growth, metabolism and antibiotic susceptibility of prokaryotic as well as eukaryotic microbes [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%